Penerapan Media Pohon Kata untuk Meningkatkan Kemampuan Berbahasa dalam Membaca pada Anak Kelompok B1 di TKN Pembina Ampenan - Nurhayati Nurhayati (Indonesian Journal of Elementary and Childhood Education, 2023)
The Class Action Research Report with the title "Application of Word Tree Media to Improve Language Skills in Reading in Group B1 Children at TKN Pembina Ampenan" was written by Nurhayati, Pre-Service PPG Program, Department of Early Childhood Education, Mataram University. Keywords: Application of Word Tree Media to Improve Language Skills in Kindergarten B1 Children at Kindergarten Pembina Ampenan. This research was motivated by the large number of B1 children who could not read words, could only read letters and learning activities using word trees as a medium had never been carried out at B1, as well as in preparation for entering elementary school. Therefore, researchers conducted research on the topic of applying word tree media in the hope of improving students' language skills, especially children's reading skills. The formulation of the problem is 1) What are the steps for implementing word tree media to improve language skills in group B1 children at TKN Pembina Ampenan for the 2022/2023 academic year. 2) Can the application of word tree media improve the language skills of group B1 children at Kindergarten Pembina Ampenan for the 2022/2023 academic year. This research is Classroom Action Research (PTK) which consists of two cycles. The data used during the research process comes from observation and documentation data, and field notes. Meanwhile, the data analysis techniques used include data reduction, data display, and conclusion drawing. The results of the research are 1) Application of word tree media to improve language skills in reading in group B1 children at TKN Pembina Ampenan for the 2022/2023 academic year, the research will take place over 2 cycles, namely cycle I and cycle II. Each cycle discusses how to improve children's language skills in reading through word trees. In carrying out this research, each cycle is divided into three activity stages, namely (1) initial activities (2) core activities (3) closing activities. 2) The results of applying word tree media can improve language skills in reading in group B1 children at Kindergarten Pembina Ampenan for the 2022/2023 academic year as evidenced by the results of the average observation of teacher activities in cycle I by 50%, an increase in cycle II by 80% with an average score for Cycle II of 3.96. Based on the results of this research, it can be concluded that the application of word tree media can improve language skills in reading in group B1 children at Kindergarten Pembina Ampenan Kata.